PENYIMPANGAN UNSUR LEKSIKAL BAHASA PAK PAK DALAM KARANGAN - Ramadhani F Pasaribu (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
Interference as deviation phenomenon of language pattern thathappened in someone who can speak two more languages. Interference asdeviation cause the unsure which is absorbed by a language is already exist inpattern of languages. Between traditional and Indonesia languages still influenceseach other if both apply and it will appear forever. This research is aimed todescribing interference unsure in Pakpak lexical in writing of state Junior HighSchool 2 Satu Atap Siempat Rube West Pakpak in learning Indonesia language.This research was taken in state Junior High School 2 Satu Atap Siempat RubeWest Pakpak. The source of research have fifty two student, two classes, and allstudent as subject of research.After all the data collected and continued by discussing the research, somay be conclude that lexical unsure was affected by interference with details ofnoun lexical unsure as big as 84,61%, and the Verb in Pakpak language toIndonesia language in writing of Indonesia have low categorize with presentationas big as 46,13%, then lexical unsure of attribute word in Pakpak language toIndonesia language have low categorize as big as 48,07%. Base on the researchthat may be conclude that inference unsure lexical in Pakpak language toIndonesia language in writing’s student is low.